In-situ monitoring of homogeneously catalysed reactions using raman spectroscopy inside hollow-core photonic crystal fibres - Schorn, Florian; Aubermann, Manfred; Zeltner, Richard; Wasserscheid, Peter; Haumann, Marco; Joly, Nicolas (Optics InfoBase Conference Papers, 2020)
We monitor the reaction of an acid with an alcohol inside a hollow-core photonic crystal fibre using Raman spectroscopy. The method uses tiny amount of chemicals and allows precise measurement of the activation energy.
CRIS-Team Scopus Importer:2020-11-13

Measurement of Minute Liquid Volumes of Chiral Molecules Using In-Fiber Polarimetry - Schorn, Florian; Essert, Arabella; Zhong, Yu; Abdullayev, Sahib; Castiglione, Kathrin; Haumann, Marco; Joly, Nicolas (Analytical Chemistry, 2023)

Online Monitoring of Microscale Liquid-Phase Catalysis Using in-Fiber Raman Spectroscopy - Schorn, Florian; Aubermann, Manfred; Zeltner, Richard; Haumann, Marco; Joly, Nicolas (ACS Catalysis, 2021)
We report on the use of hollow-core photonic crystal fibers to monitor the evolution of chemical reactions. The combination of tight confinement and long interaction length allows single-pass spectroscopic measurements using less than a microliter volume of chemicals with good accuracy. As a proof of principle, we used here nonlinear Raman spectroscopy for a reaction screening of the acidic catalyzed esterification of methanol and acetic acid.
CRIS-Team Scopus Importer:2021-07-02
Keywords: esterification; hollow-core photonic crystal fibers; in situ spectroscopy; microreactor; Raman